Admission Systolic Blood Pressure and Outcomes in Preterm Infants of ≤ 26 Weeks' Gestation - Lyu, Yanyu; Ye, Xiang Y.; Isayama, Tetsuya; Alvaro, Ruben; Nwaesei, Chuks; Barrington, Keith; Lee, Shoo K.; Shah, Prakesh S.; for the Canadian Neonatal Network Investigators (American Journal of Perinatology, 2017)
Objective To examine the relationship between admission systolic blood pressure (SBP) and adverse neonatal outcomes. Specifically, we aimed to identify the optimal SBP that is associated with the lowest rates of adverse outcomes in extremely preterm infants of ≤ 26 weeks' gestation.Methods In this retrospective study, inborn neonates born at ≤ 26 weeks' gestational age and admitted to tertiary neonatal units participating in the Canadian Neonatal Network between 2003 and 2009 were included. The primary outcome was early mortality (≤ 7 days). Secondary outcomes included severe brain injury, late mortality, and a composite outcome defined as early mortality or severe brain injury. Nonlinear multivariable logistic regression models examined the relationship between admission SBP and outcomes.Results Admission SBP demonstrated a U-shaped relationship with early mortality, severe brain injury, and composite outcome after adjustment for confounders (p < 0.01). The lowest risks of early mortality, severe brain injury, and composite outcome occurred at admission SBPs of 51, 55, and 54 mm Hg, respectively.Conclusion In extremely preterm infants of ≤ 26 weeks' gestational age, the relationship between admission SBP, and early mortality and severe brain injury was “U-shaped.” The optimal admission SBP associated with lowest rates of adverse outcome was between 51 and 55 mm Hg.
Keywords: systolic blood pressure; small for gestational age; preterm; neonatal outcomes